Local Election During the Covid-19 Outbreak: Inclusivity and Challenges for Voters with Disabilities - Amrurobbi, Azka Abdi; Sutrisno, Evi Lina (Politicon : Jurnal Ilmu Politik, 2022)
This study discusses the inclusiveness and challenges of voters with disabilities in the implementation of local election (Pilkada) during the Covid-19 outbreak. There are two things that need to be considered when implementing the 2020 local election, namely community participation, especially persons with disabilities and the application of health protocols. This study uses a qualitative research method with case study and a virtual ethnographic approach. The author focuses on the implementation of the 2020 local election in Sleman regency. In addition, the authors focus on three stages of local election, namely the stage of voter list matching and research (Coklit), campaign and socialization, and voting day. The results of the study show that political rights for voters with disabilities are regulated in several regulations, both at the international and national level. In addition, the General Election Commission (KPU) of Sleman Regency has carried out several preparations in the implementation of the 2020 local election during Covid-19 outbreak, such as conducting rapid tests for ad hoc organizers, conducting socialization and discussions with voters with disabilities, preparing health protocols at each stage, up to ensuring polling stations are accessible and inclusive. However, voters with disabilities experience several challenges based on the variety of diffabilities in each stage. The author also found several challenges experienced by voters with disabilities in accordance with the variety of disabilities, both motivated by Covid-19 outbreak, as well as challenges that have often occurred from local election to local election. It is hoped that all stakeholders involved, especially in the Local Election, can have an inclusive perspective, so that the Local Election is more friendly to voters with disabilities.